Psychosocial impact of dental appearance and associated factors among 15 year old school children in Anuradhapura municiple area - Ranasinghe, N (My University, 2009)
Cluster sampling metod combined with probability proportionate to size technique was used to select the sample. The data were collected through a self administrated questionnaire (PIDAQ) Informed consent of the parents was obtained prior to conduct the study. According to the results obtained 37 percent of students were psychosocially affected due to their dental appearance. Sex, type of school attending, highest level of parental educational attainment and paternal occupation status were the only socio-demographic variables significantly associated with the psychosocial impact of dental appearance. Since substantial proportion of school children were psychosocially affectd the knowledge about the extent and significance of psychosocial impact is important for the planning and evaluation of treatment and preventive options. On the basis of results, it is reasonable to suggest that psychosocial dimensions, different perceived oral health problems, perceived need for oral care and some socio-demographic characteristics should be considered simultaneously during assessment of oral health needs of adolescents.